Pore connectivity characterization of shale using integrated wood's metal impregnation, microscopy, tomography, tracer mapping and porosimetry. (1st January 2020) - Zhao, Jianhua; Hu, Qinhong; Liu, Keyu; Jin, Zhijun; Dultz, Stefan; Kaufmann, Josef; Fan, Yuchen
Abstract: The pore connectivity of tight shale reservoirs plays an essential role in the movement of shale gas and oil, however, the characteristics of connected pores in shale with a multi-scale and coupled pore-fracture system are poorly constrained. Working with typical American (Barnett and Eagle Ford) and Chinese (Longmaxi) shale samples in 2D/3D spaces at nano- to mm-scales, connective pores were intruded with a molten alloy (Wood's metal; WM) under a temperature of 85 °C and high pressure (60, 300, and 600 MPa) conditions. After solidification of the alloy at room temperature, polished sections were used to map WM components by field emission-scanning electron microscopy (SEM), micro- and nano-X-ray tomography and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). These tests were supplemented with mercury intrusion porosimetry (MIP) for pore-fracture throat size distribution. The shale matrix is generally characterized by low pore connectivity; however, the extent of connectivity within μm-sized and dispersed organic matter (OM) particles is high, with the observed WM-filled pore space ranging from 10% to 70% (averaged at 43%) for the Barnett Shale sample. The grain-edge fractures are important channels to connect multiple OM-hosted pore systems dispersed in shale matrix. Our work illustrates that shales exhibit a dual-connectivity behavior, with the effective porosity decreasing sharply as the distance from the sample boundary increases; the good pore connectivity zone away from the edge of sample is 500 μm under a pressure of 600 MPa for the Barnett Shale sample.